The humanistic use of social media strategies for tourism and hospitality industry promotion - Asshofi, Izza Ulumuddin Ahmad (Surya Hijau Manfaat, 2025)
This study examines communication and promotional strategies in the hospitality and tourism sectors, emphasizing the strategic use of social media to achieve specific marketing objectives and to enhance relationships between tourism managers and tourists. In the digital era, social media functions as an essential tool that facilitates access to information about tourism destinations and hospitality services for prospective travelers and hotel guests. This research adopts a qualitative methodology, enriched by a humanistic perspective, to gain a deeper understanding of tourism participants' behaviors and expectations. The findings indicate that social media plays a crucial role in promoting tourism and hospitality businesses by fostering meaningful engagement and sustaining relationships between operators and stakeholders over both short- and long-term periods. Furthermore, the integration of social media into promotional efforts enables more personalized, accessible, and location-independent communication, thereby improving the overall effectiveness of tourism marketing strategies on a global scale.